Estudo transversal sobre problemas de comportamento, desempenho acadêmico e competências sociais em escolares do Ensino Fundamental I - Sant´ana, Nathália Zoli (2012)
In several countries, prevention of behavioral problems in childhood has become a priority in health and educational public policies due to the elevation of rates of mental health problems. Studies show the importance of early intervention as an efficient strategy for the prevention of interruption of the course of behavioral problems in this stage of life. Behavioral problems can be divided into two groups: externalizing and internalizing. Studies indicate associations between the occurrence of behavioral problems in childhood and adolescence and the presence of academic difficulties and socialization problems. The general objective of the present study was to verify the association among emotional and behavioral problems, academic performance and indicators of social competence in a group of school children. A cross-sectional study was developed based in a non-probabilistic sample composed of 181 children, age range 6-12 years old, enrolled in an elementary school in São Paulo, and their respective parents. Data collection instruments were: a) Child Behavior Checklist for Ages 6-18 (CBCL/6-18); and b) Recording of academic performance through the identification of annual average grades in Mathematics and Portuguese. For data analysis two softwares were used: Statistical Package for the Social Sciences (SPSS), version 15.0, and Assessment Data Manager. Pearson correlation analyses were carried out to verify associations between the group s descriptive variables and raw scores in CBCL/6-18, as well as ANOVAS to verify possible differences between age groups and gender according to the number of behavioral problems and social competence with CBCL/6-18. A logistic regression analysis was carried out for creating a pattern that determines the probability for a child to be classified as borderline or clinical in CBCL/6-18 scale of total emotional and behavioral problems, having as predictive variables age, gender, academic performance through recording of grades in Mathematics and Portuguese, and raw scores in CBCL/6-18 scales of social competences. The main results indicate that in the total sample, the main behavioral problems are concentrated in the scales of anxiety and depression, anxiety problems, emotional problems, internalization problems and total emotional/behavioral problems. Positive and statistically significant correlation coefficients were verified between academic performance according to parental report in CBCL/6-18 and academic performance recorded through grades in Mathematics and Portuguese. Among the last two variables and attention problems and problems of attention deficit and hyperactivity of CBCL/6-18 it was identified negative and statistically significant correlation coefficients. In the scale of competences in academic performance of CBCL/6-18, the ANOVA indicated statistically significant differences between both age groups (6-8 and 9-12 years old). Only in the scales of somatic complaints, somatic problems, anxiety and depression, internalization problems and attention problems, the ANOVA identified statistically significant differences between boys and girls. The final logistic regression model, generated for the sample, verified that the probability of socialization problems and total emotional/behavioral problems in the borderline or clinical levels is of approximately 76%. The probability of academic performance problems in Mathematics and total emotional/behavioral problems in the borderline or clinical levels is of approximately 73%. We conclude that the study has allowed verifying the association between behavioral problems and academic difficulties in the sample. The outcome of the generated logistic regression model allows inferring that academic difficulties and socialization problems can be predictive factors that raise the probability to the development of emotional and behavioral problems.